Analisis Faktor-faktor yang Mempengaruhi Nilai Tukar Petani Komoditas Nilam di Provinsi Aceh - Muhammad Abdillah Sinaga; Muhammad Yuzan Wardhana; Mustafa Usman (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
The plantation sub-sector is one of the sub-sectors that has great potential in the agricultural sector of Aceh Province. This is evidenced by the plantation sub-sector capable of contributing 32.43% of the total GRDP of the agricultural sector. Based on the status of exploitation, the plantation sub-sector in Indonesia is divided into smallholder plantations (PR), large state plantations (PBN) and large private plantations (PBS). One of the plantation commodities that have potential in Aceh Province is patchouli. Aceh is able to fully contribute to Indonesia's patchouli production with a contribution of 18.78%. Patchouli Aceh has special features compared to other patchouli. Patchouli Aceh is able to produce high yields, which is around 2.5-5% while other patchouli are only able to produce yields of 1-2%. The farmer's exchange rate (NTP) of patchouli as an indicator of the level of welfare of patchouli farmers shows an index that is still low and even continues to decline. This condition shows that the developed agribusiness system has not fully prospered the farmers. Various factors, both internal and external, can affect the exchange rate of farmers.This study aims to identify the factors that influence the exchange rate of patchouli farmers in Aceh Province. The object of this research is the exchange rate of patchouli farmers. The type of data used is secondary data in the form of a time series with a range of 2010-2020 which is sourced from various literatures and related agencies. The analytical method used is multiple linear regression analysis method to analyze the factors that affect the exchange rate of patchouli farmers in Aceh Province. The model testing carried out includes the normality test, autocorrelation, multicollinearity, heteroscedasticity, coefficient of determination, F test to determine the effect of variables simultaneously and T test to determine the effect of variables partially.Based on the results of the analysis, it was found that the variables of productivity, patchouli prices at the farm level and GRDP in the agricultural sector had a significant effect, while inflation at the rural level had no significant effect on the exchange rate of patchouli farmers. Productivity, patchouli prices at the farm level and GRDP in the agricultural sector have a positive relationship to the patchouli farmer's exchange rate while inflation at the rural level has a negative relationship to the patchouli farmer's exchange rate.